2011
DOI: 10.2134/agronj2010.0185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irrigation, Cultivar, and Plant Density on Cotton Within‐Boll Fiber Quality

Abstract: This study was designed to determine how within‐boll fiber quality of cotton (Gossypium hirsutum L.) is affected through irrigation, cultivar, and plant density management. Field experiments were conducted in 2006 and 2007 using two contemporary cultivars, arranged in a split‐split plot design with two irrigation rates (6.33 and 4.32 mm d−1) as the main plot, plant density (79,071; 128,490; 197,677 plants ha−1) as the subplot, and cotton cultivar (FM9063B2RF and ST4554B2RF) as the subsubplot. Plants from 3 m o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…For the interaction between the factors, considering the water deficit versus sampling, the interaction was not significant for the STR and ELG parameters, while the cultivar versus sampling interaction was significant only for the UHM data. These results proved that there is variation in cotton fiber quality within the same plant, depending on the boll position, as discussed by several authors, such as Bradow and Davidonis (2000), Bauer et al (2009) andFeng et al (2011).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…For the interaction between the factors, considering the water deficit versus sampling, the interaction was not significant for the STR and ELG parameters, while the cultivar versus sampling interaction was significant only for the UHM data. These results proved that there is variation in cotton fiber quality within the same plant, depending on the boll position, as discussed by several authors, such as Bradow and Davidonis (2000), Bauer et al (2009) andFeng et al (2011).…”
Section: Resultssupporting
confidence: 80%
“…Additionally, for experiments or field appraisal, in which cotton plants endured abiotic stresses, water deficit is the best way to estimate cotton fiber quality in harvesting the whole plant. Environmental variation that occurs within the plant canopy, between plants and between plots, causes great variability in fiber quality characteristics, not only at boll level, but also among plants and plots (Bauer et al, 2009;Bradow and Davidonis, 2000;Feng et al, 2011). In this way, the more uniform and representative the conditions of the plant and the plot as a whole is with the sampling, the more representative the results of the fiber quality analysis will be.…”
Section: Resultsmentioning
confidence: 99%
“…Ashley (1972) reported that fruits produced at the top canopy position likely receive less carbohydrate because they are initiated late in the growing season. Also, Feng et al (2011) reported that different seeds within a boll produce different fiber quality. Management practices such as planting date (Davidonis et al, 2004), plant population (Bednarz et al, 2006), and irrigation rate (Feng et al, 2010) can influence specific canopy positions and the within-canopy distribution of fiber properties in a cotton plant.…”
Section: Evaluating Within-plant Variability Of Cottonmentioning
confidence: 99%
“…Therefore, the indeterminate growth habit of cotton plants is one of the most important contributors to the within-plant variability of cotton fiber quality. Additionally, growth conditions have an impact on the within-canopy variation of fiber quality, in particular on fiber maturity distribution (Ritchie et al, 2004;Feng et al, 2011). Fiber maturity is one of the most important fiber quality parameters as it has a potential impact on different fiber properties including fiber length, strength, the linear density of fiber or fineness, and other yield components such as cotton fiber density (Ayele et al, 2017).…”
Section: Evaluating Within-plant Variability Of Cottonmentioning
confidence: 99%
See 1 more Smart Citation